2016
DOI: 10.1016/j.neuropharm.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet augments amphetamine sensitization in mice: Role of feeding pattern, obesity, and dopamine terminal changes

Abstract: High fat (HF) diet-induced obesity has been shown to augment behavioral responses to psychostimulants that target the dopamine system. The purpose of this study was to characterize dopamine terminal changes induced by a HF diet that correspond with enhanced locomotor sensitization to amphetamine. C57BL/6J mice had limited (2hr 3d/week) or extended (24h 7d/week) access to a HF diet or standard chow for six weeks. Mice were then repeatedly exposed to amphetamine (AMPH), and their locomotor responses to an amphet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 65 publications
9
28
1
2
Order By: Relevance
“…32 Mice with access to high fat gained ~2.5 times more weight than control-chow-fed littermates over the 6 weeks, replicating the weight gain observed in previous studies, which resulted in hyper-insulinemia, 33 hyperleptinemia, 34 and elevated serum triglycerides. 31 Significant differences in body weight were detected as early as 3 weeks ( p < 0.01), with final averaged body weights of 24.88 ± 1.16 and 31.36 ± 3.06 g for control and high-fat-fed mice, respectively ( p < 0.001) (Figure 1B). Two-way analysis of variance (ANOVA) detected main effects of time ( F 18,324 = 127.36, p < 0.0001) and diet ( F 1,324 = 15.33, p = 0.001) with a time × diet interaction ( F 18,324 = 27.09, p < 0.0001).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…32 Mice with access to high fat gained ~2.5 times more weight than control-chow-fed littermates over the 6 weeks, replicating the weight gain observed in previous studies, which resulted in hyper-insulinemia, 33 hyperleptinemia, 34 and elevated serum triglycerides. 31 Significant differences in body weight were detected as early as 3 weeks ( p < 0.01), with final averaged body weights of 24.88 ± 1.16 and 31.36 ± 3.06 g for control and high-fat-fed mice, respectively ( p < 0.001) (Figure 1B). Two-way analysis of variance (ANOVA) detected main effects of time ( F 18,324 = 127.36, p < 0.0001) and diet ( F 1,324 = 15.33, p = 0.001) with a time × diet interaction ( F 18,324 = 27.09, p < 0.0001).…”
Section: Resultsmentioning
confidence: 97%
“…High fat-fed mice have an increased ratio of cytosolic to membrane DAT, but greater overall DAT in tissue lysate from the NAc. 31 Improving insulin signaling in high fat insulin-resistant mice putatively supports redistribution of the DAT to the plasma membrane where a functional increase in DAT activity can be measured with voltammetry. To rule out the possibility that high-fat mice simply had reduced insulin receptor content in the NAc, we used a quantitative ELISA to measure total insulin receptor protein in the NAc ( n = 7, controls; n = 8, high fat).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, sucrose consumption during adolescence leads to long-lasting deficits of reward processing (Frazier et al, 2008; Vendruscolo et al, 2010; Naneix et al, 2016) and HFD consumption in adolescent but not adult rats increases locomotor sensitivity to psychostimulants (Baladi et al, 2015; Fordahl et al, 2016), suggesting a particular impact of high-energy diet consumed during adolescence on the DA system (Reichelt, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Here we have two facts: (1) The chronic exposure to HSD was not able to sensitize the dopaminergic system. It is possible that a different temporal pattern of availability would have a distinct outcome on the diet effects concerning the dopaminergic system (Fordahl et al, 2016). Accordingly, studies using intermittent access to high palatable food showed greater AMPH‐locomotor response than those using a chronic availability (Avena et al, 2012; Fordahl et al, 2016).…”
Section: Discussionmentioning
confidence: 99%